2015
DOI: 10.1159/000375177
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Motor Cortex Stimulation for Neuropathic Pain in 23 Patients

Abstract: Background: Motor cortex stimulation (MCS) is being offered to patients suffering from neuropathic pain. Outcome prediction, programming and especially sustaining a long-term treatment effect represent major challenges. We report a retrospective long-term analysis of our patients treated with MCS over a median follow-up of 39.1 months. Objectives: To investigate the time course of the treatment effect in MCS for neuropathic pain. Methods: Twenty-three closely followed patients treated with MCS were retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
1
10
0
2
Order By: Relevance
“…Risk of bias as assessed by the RoB2 showed that all included papers had a low overall risk-of-bias judgement 47,[75][76][77] . Risk of bias as assessed by the ROBINS-I showed that all included papers had a moderate overall risk-of-bias judgement 9,10,13,24,40,[42][43][44][45]55,[78][79][80][81][82][83][84][85][86] . Table 1 provides an overview of the quality of the evidence of the included papers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Risk of bias as assessed by the RoB2 showed that all included papers had a low overall risk-of-bias judgement 47,[75][76][77] . Risk of bias as assessed by the ROBINS-I showed that all included papers had a moderate overall risk-of-bias judgement 9,10,13,24,40,[42][43][44][45]55,[78][79][80][81][82][83][84][85][86] . Table 1 provides an overview of the quality of the evidence of the included papers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Three recent publications, including one by our group, were focused on the outcomes and challenges of long‐term MCS for pain . A gradual increase in required stimulation intensity is frequently observed, and loss of treatment effect is not uncommon following years of stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Nuti et al [18] suggested that the first month result was a predictor of long-term results. Nevertheless, Slotty et al [19] concluded that short-term response did not predict long-term results. In this report, we observed a statistically significant reduction in the total NPSI score after MCS and a strong positive correlation between the remission rates based on the NPSI and VAS scores.…”
Section: Discussionmentioning
confidence: 99%